Parametric Trigger Signal Generation with Microcontroller and FPGA Based Architectures - Kazma, Coskun; Levent, Vecdi Emre; Aydin, Nizamettin (IEEE, 2019)
A new system to obtain information from the central nervous system has been developed. Our system consists of two main components. The first of these components is the machine, which is located on the index and middle finger tips, stimulating mechanoreceptors according to the test protocol. The other is a personal computer running a desktop software for the implementation of test protocols. The flow is as follows. The subjects are asked the question of the test protocol through the personal computer. The parameters are then transmitted to the embedded system board on the machine. The embedded system board takes step motors to apply the relevant test parameters. The desktop software expects the subject to answer the question using the right and/or the left mouse button of the computer mouse. After answering the relevant question, the test proceeds to the next step. According to the test protocol, the stimulation process of the mechanoreceptors located at the index and middle finger tips must start and terminate at the same time. From this perspective, the embedded system board with 3 18F46K22 PIC microcontrollers produces 2 square wave signals with different frequencies and amplitudes simultaneously. The embedded system card developed with the PIC microcontroller is also implemented on an FPGA. The system has also been tested on 24 blue- and white-collar employees and a significant result has been obtained.
Keywords: Parallel square wave generation; Tactile Stimulator; FPGA; Computer Science